Distinct alpha‐Synuclein species induced by seeding are selectively cleared by the Lysosome or the Proteasome in neuronally differentiated SH‐SY5Y cells. Issue 6 (22nd September 2020) - Pantazopoulou, Marina; Brembati, Viviana; Kanellidi, Angeliki; Bousset, Luc; Melki, Ronald; Stefanis, Leonidas
Abstract: A major pathological feature of Parkinson's disease (PD) is the aberrant accumulation of misfolded assemblies of alpha‐synuclein ( α ‐Syn). Protein clearance appears as a regulator of the ' α ‐Syn burden' underlying PD pathogenesis. The picture emerging is that a combination of pathways with complementary roles, including the Proteasome System and the Autophagy–Lysosome Pathway, contributes to the intracellular degradation of α ‐Syn. This study addresses the mechanisms governing the degradation of α ‐Syn species seeded by exogenous fibrils in neuronally differentiated SH‐SY5Y neuroblastoma cells with inducible expression of α ‐Syn. Using human α ‐Syn recombinant fibrils (pre‐formed fibrils, PFFs), seeding and aggregation of endogenous Proteinase K (PK)‐resistant α ‐Syn species occurs within a time frame of 6 days, and is still prominent after 12 days of PFF addition. Clearance of α ‐Syn assemblies in this inducible model was enhanced after switching off α ‐Syn expression with doxycycline. Lysosomal inhibition led to accumulation of SDS‐soluble α ‐Syn aggregates 6 days after PFF‐addition or when switching off α ‐Syn expression. Additionally, the autophagic enhancer, rapamycin, induced the clearance of α ‐Syn aggregates 13 days post‐PFF addition, indicating that autophagy is the major pathway for aggregated α ‐Syn clearance. SDS‐soluble phosphorylated α ‐Syn at S129 was only apparent at 7 days of incubation with a higher amount of PFFs. Proteasomal inhibition resulted in further accumulation of SDS‐soluble phosphorylated α ‐Syn at S129, with limited PK resistance. Our data suggest that in this inducible model autophagy is mainly responsible for the degradation of fibrillar α ‐Syn, whereas the proteasome system is responsible, at least in part, for the selective clearance of phosphorylated α ‐Syn oligomers. Abstract : Different degradation pathways induce the clearance of distinct α ‐Syn aggregated species. Upon incubation with recombinant fibrils (PFF), endogenous α ‐Syn aggregates are formed and Autophagy serves as the major pathway for clearance. pS129 α ‐Syn oligomers are apparent only upon incubation with high‐dose PFFs, and the Proteasome system is implicated in the degradation process. Our findings represent new and important insights into the biology of α ‐Syn aggregation and turnover.